Updating Balanced Scorecard Model for The Evaluation of The Strategic Performance in Greater Amman Municipality - Al-haj Ahmad, Fadia B.; H. Atieh, Sulyman (European Scientific Journal, ESJ, 2016)
This study aimed to develop and update the model of Balance Scorecard (BSC) to measure the strategic performance efficiency at Greater Amman Municipality (GAM). In addition, the study objectives include the following: (1) To identify the availability of the BSC requirements in GAM; (2) To develop a set of measures that are in line with municipal work; and (3) To add to the BSC Model of the environmental requirements as a fifth perspective. In achieving these objectives, a questionnaire was developed based on theoretical review, previous studies, and the work experience of the authors in GAM. The questionnaire includes many items which covered five perspectives of BSC, and it was distributed to the study participants who were responsible for preparing and reviewing Strategic plan of GAM and other responsible employees in GAM. After determining the descriptive statistics and after the testing of the hypotheses, the study concluded that there is a statistical significant impact of all independent variables (customer perspective, financial perspective, environmental perspective, internal processes perspective, and learning and growth perspective) based on the efficiency of strategic performance in Greater Amman Municipality.